Sustainability Literacy and Implementation Intentions Among Business Study Students: A Strategic Business Perspective - Kohilawattage, Dayan (My University, 2025)
This thesis examines the relationship between sustainability literacy in graduate students and how this translates into implementation intentions in a strategic business environment. Although sustainability education is gradually becoming part of higher education, a limited amount of information is available regarding how students transition beyond awareness to action, especially in a manner that is consistent with long-term strategic thinking. As the main theoretical framework, the Dynamic Capabilities Theory (DCT) is used to examine the way in which students can acquire sensing, seizing, and transforming capabilities concerning sustainability; the supporting theories are Theory of Planned Behavior (TPB) and Transformative Learning Theory (TLT). The data were gathered by using semi-structured interviews with ten students in the master level in universities located in Vaasa, Finland. Thematical analysis indicated that students were highly aware (sensing) and increasingly motivated to incorporate sustainability in their careers (seizing), and were actually doing something to implement sustainable practices in their academic, personal, or professional environments (transforming). Results indicate that sustainability literacy is a knowledge base and the source of capabilities development that can affect future strategic decision-making. The study becomes a valuable contribution to gaining deeper insight into the process of trans-forming students into sustainability-oriented professionals by merging DCT with behavioral and learning theories. This study has practical implications to the universities that want to more actively promote sustainability education, as well as to businesses that want to produce future leaders who would have sustainability competencies. It also demonstrates the necessity of more amalgamated and considerate pedagogies which transcend theoretical teaching and promote practical implementation.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development